UHPLC‐Q‐TOF‐MS/MS‐guided dereplication to study chemical constituents of Hedera nepalensis leaves in northern Vietnam - Pham Hong Ngoc; Tran Chieu An; Nguyen Tuan Hiep; Tran Phan Huynh Nhu; Le Ngoc Hung; Nguyen Quang Trung; Bui Quang Minh; Phung Van Trung (Journal of Analytical Science and Technology, 2023)
Abstract Hedera nepalensis is commonly used as a traditional medicine for the treatment of several diseases. In this research, the efficient characterization of chemical constituents, especially triterpenoid saponins, contained in H. nepalensis extract was established by applying ultra‐high‐performance liquid chromatography‐quadrupole time‐of‐flight tandem mass spectrometry method (UHPLC‐Q‐TOF‐MS/MS). As a result, a total of 45 compounds including 21 triterpene saponins were tentatively elucidated based on MS and MS/MS data, in which eight structures have been reported for the first time. This study provided an efficient analysis strategy to rapidly determine the chemical constituents and laid a foundation for future study of H. nepalensis planted in Northern Vietnam and other Hedera species.